(untitled) (Bangladesh Journal of Microbiology, 2019)
Yellow fever virus is a prototype member of the Flaviviridae family causing high fever and jaundice. Though YF 17D vaccine is administered to yellow fever patients, however it can produce adverse effects in immunocompromised, older people and young infants. The aim of this study is to design an epitope-based peptide vaccine by targeting envelope (E) protein of Yellow Fever Virus. Thirty sequences of E protein of Yellow Fever Virus strains were retrieved from NCBI database. E protein was found to be mostly conserved among all the sequences with little variability and also was identified as a probable antigen. Different epitope prediction tools predicted 4 common epitopes, 3 of which were found to be antigenic. A peptide VKNPTDTGin E protein was predicted to have surface accessibility which overlaps with the VKNPTDTGHGT epitope.So, the whole VKNPTDTGHGT epitope was taken for further analysis. The VKNPTDTGHGT epitope showed 96.67% conservancy and also possesses flexibility, hydrophilicity and non-toxicity. Therefore, VKNPTDTGHGT can be regarded as a potential vaccine candidate against Yellow fever virus with further in vitro and in vivo validation. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 27-35